2000
DOI: 10.3349/ymj.2000.41.3.362
|View full text |Cite
|
Sign up to set email alerts
|

Issues and problems of adaptation of North Korean defectors to South Korean society: an in-depth interview study with 32 defectors

Abstract: The number of North Koreans defecting to South Korea is increasing rapidly. They are important people to South Korean society not only for humanitarian reasons, but also for their impact on the future Korean unification and the integration of the two different South and North Korean peoples. However, the defectors have experienced many difficulties in their adaptation to South Korean society due to their own characteristics and due to the misunderstandings of the South Korean people. To obtain comprehensive qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Recent studies have reported on the vicious circle that exists between the mental health and PTSD symptoms in refugees and their living conditions in their new environment (Kivling-Boden, & Sundbom, 2002;Lavik, Hauff, Skrondal, & Solberg, 1996). It also has been reported that defectors experience psychological difficulties and economic hardships in the process of adapting themselves to South Korean society (Jeon, 1997b(Jeon, , 2000. Therefore, the evaluation of the trauma experienced by defectors while adapting themselves to South Korea will be discussed in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported on the vicious circle that exists between the mental health and PTSD symptoms in refugees and their living conditions in their new environment (Kivling-Boden, & Sundbom, 2002;Lavik, Hauff, Skrondal, & Solberg, 1996). It also has been reported that defectors experience psychological difficulties and economic hardships in the process of adapting themselves to South Korean society (Jeon, 1997b(Jeon, , 2000. Therefore, the evaluation of the trauma experienced by defectors while adapting themselves to South Korea will be discussed in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…Refugees may find resettling in a new society difficult due to limitation of occupational opportunities [70]. Moreover, language and cultural differences between the two Koreas [71] may be important factors that aggravate social isolation. North Korean refugees consider economic independence as the most important condition for living in South Korean society [72].…”
Section: Covariatesmentioning
confidence: 99%
“…In addition to employment issues, North Korean refugees face language and cultural barriers [71] (p. 4). In the past 50 years, the two Koreas have seen significant changes in their respective cultures and languages.…”
Section: Covariatesmentioning
confidence: 99%
“…Korea, due to its post civil war division, has been preoccupied with the peaceful unification of the country. Although the two Koreas, prior to their division, share a common history, language and traditional values, their prolonged separation has produced two different peoples living by different social and cultural norms (JEON, 2000). This paper argues that global citizenship education is more applicable to Korea as the concept of embracing cultural diversity, since it would increase Koreans' understanding of each other, may help to build momentum towards a future peaceful unification with North Korea.…”
Section: Increasing Cultural Diversity and Importance Of Global Citizmentioning
confidence: 99%